Tourism Sector Development Through Dynamic Location Quotient and Shift Share Analysis: Pengembangan Sektor Pariwisata Melalui Analisis Dynamic Location Quotient dan Shift Share - Rizky, Indah Mutiara; Imsar, Imsar; Harahap, Muhammad Ikhsan (Indonesian Journal of Innovation Studies, 2025)
General Background: Economic disparities between regions in Indonesia remain a persistent development challenge. Specific Background: Langkat Regency, situated within North Sumatra Province, reflects a localized case of uneven growth requiring focused assessment. Knowledge Gap: Limited studies have examined sector-specific contributions, particularly the "Other Services" sector, to regional growth using comparative and quantitative frameworks. Aims: This study aims to analyze and compare economic development and inequality between North Sumatra Province and Langkat Regency, focusing on the 2021–2024 period. Results: Utilizing data from the Central Statistics Agency (BPS) and applying the Dynamic Location Quotient (DLQ) and shift-share methods, the analysis reveals an average increase of IDR 14.87 billion in the Other Services sector, with a shift-share contribution of IDR 2.07 billion from 2023 to 2024. Novelty: The study integrates DLQ and shift-share analysis to isolate and evaluate the basic sector's dynamics within a regency-province framework, an approach not commonly applied in prior research on Langkat. Implications: These findings indicate robust sectoral growth potential and provide an empirical foundation for regional economic planning, emphasizing the strategic development of the Other Services sector to reduce intra-provincial inequality and enhance local economic resilience. Highlights: Highlights the growth potential of the Other Services sector in Langkat Regency. Uses DLQ and shift-share methods for sector-based economic comparison. Offers strategic insights for reducing regional economic disparities. Keywords: Regional Development, Economic Inequality, DLQ, Shift-Share Analysis, Other Services Sector